Assessing the potential of spider plant (Cleome gynandra L.) as a trap crop for the management of specialist feeders on vegetable brassicas - Zedler, Benjamin; Srinivasan, R.; Su, F.-C. (Journal of Asia-Pacific entomology, 2016)
In a field experiment with spider plant (Cleome gynandra L.), high infestation by various brassica specialist Lepidopteron pests such as the Cabbage Head Caterpillar (CHC), Crocidolomia binotalis and Cabbage Webworm (CWW), Hellula undalis was observed. Multiple- and two-choice tests showed that Indian mustard (Brassica juncea) is the most preferred brassica species for the diamondback moth (DBM), Plutella xylostella and CWW, whereas CHCs preferred pak choi (B. rapa subsp. Chinensis). Although the brassica specialists overwhelmingly feed on spider plant, females of these brassica specialists did not lay significantly more eggs on spider plant or the most preferred brassica plants in no- and two-choice experiments. In a multiple-choice test, they did not have any significant oviposition preference for brassica plants and spider plant at either vegetative or flowering stages. CHC and DBM did not show any significant oviposition preference for young or old spider plant leaves within a plant. The volatiles from spider plant did not enhance the egg laying of these specialist feeders on their most preferred brassica species. Larval feeding experiments confirmed that spider plant was less suitable for DBM, CHC and CWW. In nethouse experiments with an increasing percentage of spider plant as a trap crop, DBM and CHC laid eggs only on the most preferred brassica species; however, the total number of eggs laid decreased with a higher percentage of spider plant. Based on the results of this study, we evaluated the potential of spider plant to serve as a trap crop. [Display omitted] •Brassica specialists overwhelmingly feed on Cleome spp.•But, female brassica specialists did not lay significantly more eggs on Cleome spp.•Volatiles from Cleome did not enhance the egg laying.•Cleome was a less suitable host plant.•Total number of eggs laid decreased with a higher percentage of Cleome.